Frequent recovery of influenza A but not influenza B virus RNA in aerosols in pediatric patient rooms. (13th April 2020) - Shiu, Eunice Yuen Chi; Huang, Wenbo; Ye, Dan; Xie, Yanmin; Mo, Jinhan; Li, Yuguo; Cowling, Benjamin John; Yang, Zifeng; Leung, Nancy Hiu Lan
Abstract: Influenza transmission occurs through the air, but the relative importance of small droplets, or aerosols, in influenza transmission especially within healthcare facilities remains uncertain. Detections of influenza virus in aerosols in cough and exhaled breath from infected patients and from the air in outpatient or inpatient healthcare facilities have been studied, but most studies were done in adults with very few data involving children. We aimed to assess the potential of influenza transmission via aerosols in pediatric patient rooms. Two‐stage cyclone (NIOSH) air samplers were used to collect the air in 5‐bed pediatric patient rooms with patients with influenza‐like illness. Influenza A virus RNA was recovered in 15/19 (79%) air sampling occasions with ≥1 patient with laboratory‐confirmed influenza A virus infections, in all air size fractions (>4 µm, 1‐4 µm and <1 µm). Influenza B virus RNA was significantly less detected (2/10 occasions, 20%). We estimated a ventilation rate of 1.46 ACH in a similar but unoccupied 5‐bed patient room. High quantities of influenza A virus RNA detected in the air in pediatric patient rooms suggests other individuals in pediatric patient rooms including other patients, visitors, caretakers and healthcare workers could be exposed to influenza A virus in aerosols while caring for infected children.